Seasonality and Recall in Labor Supply Data in Rural Malawi - International Food Policy Research Institute; Mockshell, Jonathan (International Food Policy Research Institute, 2022)
This dataset explores (1) labor supply and (2) perceptions and impacts of COVID-19 via 4 quarterly phone surveys in rural Malawi. The sample was chosen randomly from among those that reported cell phone numbers in a previous multi-topic, in person survey in several regions of rural Malawi.